Toxicity evaluation of aromatic water of Pinus eldarica Medw. in acute and sub-chronic toxicity experiments - Ostad, Seyed Nasser; Vazirian, Mahdi; Pahlevani, Roghayeh; Hadjiakhondi, Abbas; Hamedani, Morteza Pirali; Almasian, Ali; Manayi, Azadeh (Progress in Nutrition, 2018)
The plants of Pinus genus have been traditionally used in treatment of several diseases and recent studies revealed new pharmacological and biological activities of the genus. Pinus eldarica (Pinaceae) is commonly known as Tehran pine and planted in many parts of Iran, Afghanistan, and Pakistan. Aromatic water of P. eldarica needle have been used in arthritis rheumatoid complains in Iranian folk medicine. However, there is no study regarding the composition and safety of the aromatic water administration in human, therefore in the present study components of the aromatic water were identified using gas chromatography-mass spectrometry (GC-MS) method followed by evaluation of its probable acute and sub-chronic toxicity in Wistar male rats. The aromatic water was administered with dose of 10-22.5 mL/kg in acute and with dose of 10 mL/kg in sub-chronic toxicity assay for a period of 45 days. Thymol (78.8%) and carvacrol (6.2%) were characterized as the main part of the aromatic water constituents. The results indicated no sign of toxicity and lethality after single and repetitive doses of the aromatic water of the plant with the median lethal dose (LD50) higher than 22.5 mL/kg body weight for male rats. All the hematological and biochemical parameters with histological examination of liver, spleen, kidney, and lung were normal compare to normal saline. There was only significant increase in triglyceride level in the period of 23 days. Therefore, oral administration of the aromatic water of P. eldarica may considered as non-toxic at doses of 10-22.5 mL/kg. Thymol and carvacrol could possibly contribute to the beneficial effect of aromatic water of the plant in arthritis rheumatoid complains.